Reseña bibliográfica: Misión cumplida. Cómo la reforma universitaria llegó a la Constitución Nacional - Bernal, Marcelo (2024)
"Mission accomplished. How university reform was included in the National Constitution is a book recently published in 2023 in a joint edition by the University of Buenos Aires Press (Eudeba) and Ediar, authored by Dr. Gonzalo Álvarez and with a prologue by Lic. Jesús Rodríguez."